2019
DOI: 10.3758/s13414-019-01823-3
|View full text |Cite
|
Sign up to set email alerts
|

Response-level processing during visual feature search: Effects of frontoparietal activation and adult age

Abstract: Previous research suggests that feature search performance is relatively resistant to age-related decline. However, little is known regarding the neural mechanisms underlying the age-related constancy of feature search. In this experiment, we used a diffusion decision model of reaction time (RT), and event-related functional magnetic resonance imaging (fMRI) to investigate age-related differences in response-level processing during visual feature search. Participants were 80 healthy, right-handed, communitydwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 104 publications
4
13
0
Order By: Relevance
“…Non-decision time has previously been linked to fronto-parietal fMRI activity in older adults, therefore these observed findings complement and extend these results (Madden et al, 2020). Similarly, age-related increases in variability and reductions in visual functions requiring the suppression of irrelevant perceptual information were associated with individual variability in fronto-parietal white matter microstructure (Chadick et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Non-decision time has previously been linked to fronto-parietal fMRI activity in older adults, therefore these observed findings complement and extend these results (Madden et al, 2020). Similarly, age-related increases in variability and reductions in visual functions requiring the suppression of irrelevant perceptual information were associated with individual variability in fronto-parietal white matter microstructure (Chadick et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, age-related deterioration in the SLF - a white matter pathway crucial for the effective communication within the fronto-parietal attention network and hence between sensory and motor networks - is likely to contribute to the overall slowing of sensory and/or motor processing components reflected in the non-decision time. In addition, it has also been documented that older adults show reduced functional connectivity in fronto-parietal networks and that this is related to increased distractibility and diminished attentional focus with age (Campbell et al, 2012, Madden et al, 2020). Thus, the observed pattern of associations between age-related variation in non-decision time and SLF microstructure may reflect age-related difficulties in perceptual suppression or inhibition (Chadick et al, 2014) and/or a greater reliance in top-down processing as a response to diminished low-level sensory input (Lai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target identification can be enhanced when the target has increased salience, from either bottom-up (featural) or top-down (cognitive) sources (Proulx, 2007;Theeuwes, 2010), and this improvement in target identification is associated with significant deactivation, particularly in FEF (Liu & Pleskac, 2011;Madden, Siciliano, et al, 2020), analogous to priming effects (Henson, 2003;Lustig & Buckner, 2004;Schacter et al, 2007). Whereas a salient target improves performance, salient distractor items often interfere with performance, by capturing attention that could otherwise be devoted to target identification (Theeuwes, 2014;Yantis, 1996).…”
Section: During Visual Searchmentioning
confidence: 99%
“…For example, in an fMRI study investigating age-related performance in a visual search task, changes in non-decision time were associated with targets accompanied by response-incompatible distractors in the elderly group. T er was correlated with the Frontal eye fields (FEF) and dorsal fronto-parietal regions, which suggested a major contribution from the visual encoding process (Madden et al, 2019). An Electroencephalography (EEG) study of figure-ground segregation instead found a correlation between N200 latency and the non-decision component, suggesting that N200 tracks the completion of visual encoding (Nunez et al, 2019).…”
Section: Drift-diffusion Modelmentioning
confidence: 99%